The role of higher education institutions in promoting entrepreneurship development - Abdijabbar Ismail Nor; Fadumo Shafie Mohamed; Maryam Mohamed Barre; Mohamed Abdulle Hussein (Cogent Business & Management)
Entrepreneurship is increasingly recognized as a key driver of economic growth, innovation, job creation, and poverty reduction, particularly in developing and low-income economies. In response, higher education institutions (HEIs) are gaining attention for their potential to foster entrepreneurship through specialized programs, education and training, support services, research and innovation, partnerships, and community engagement. Thus, this study examines how HEIs contribute to entrepreneurship development through education and training, partnerships and collaboration, and community engagement and how these efforts align with the United Nations Sustainable Development Goals (SDGs). Using a cross-sectional research design, data were collected using a structured questionnaire distributed to 201 trainees and administrative employees at three institutions: SIMAD University, Jamhuriya University, and Benadir University. A purposive sampling technique was employed to collect comprehensive and relevant data from stakeholders involved in entrepreneurship training programs in higher education institutions (HEIs). The study utilized partial least squares structural equation modeling to test the hypotheses, with Smart-PLS software (v.4.1.0.9) employed for data analysis. The findings reveal that HEIs positively influence entrepreneurship development by fostering an entrepreneurial ecosystem through enhanced educational and training programs, strengthened community collaboration, and creation of robust networks. These findings underscore the vital role of HEIs in driving entrepreneurial growth and highlight a holistic approach to fostering entrepreneurship development by integrating education, networking, partnerships, and community support. Policymakers, HEIs, and public and private sector organizations can leverage these insights to design targeted interventions that support entrepreneurial growth and sustainability.